DIFFERENCES IN DEVELOPMENT OF INDIVIDUALS AND LANGUAGES EARLY CHILDREN REVIEWED FROM MOTHER STATUS IN KEMALA TK BHAYANGKARI 08 BAJAWA-NTT (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Family is the first environment experienced by a child when born into the world, and during preschool times, the family is the most important social agent. When many parents work, childcare shifts to close relatives, namely grandmother / grandfather, in parenting between parents and grandparent have their own characteristics, but they have the same hope that the child becomes an independent person. The purpose of this study was to determine whether there were differences in the level of early childhood independence in terms of caregiver subjects (parents and grand parenting). This study uses a quantitative method with a quasi-experimental research type, namely the experimental group and the control group are not chosen randomly but by grouping the research subjects based on the groups that have been formed. The population in this study The population targeted in this study were all kindergarten children B in Kemala Bhayangkari 08 Bajawa-NTT kindergarten. The sampling technique in this study uses purposive sampling which is carried out by sampling techniques with certain considerations. The considerations in determining the sample are the characteristics of kindergarten children A. According to Roscoe (in Sugiono, 2010), in an experimental study using experimental groups and control groups, the number of sample members of each group was between 10 s / d20. Based on this review, the number of samples in this study amounted to 40 children, of which 20 children from group A became the experimental group and 20 children from group B1 became the control group. Data analysis method of this study is analysis of variance (ANOVA) with the help of SPSS 19 for Windows. Based on the results of the study, first) The development of early childhood independence that is cared for by working mothers shows that children tend to be able to be independent without the help of teachers at 65.0% and the remaining 35.0% of children are at a level of independence capable of teacher balance. While the independence of early childhood raised by mothers who do not work shows children tend to be able to be independent without teacher assistance by 55.0%, and the remaining 40.0% and 5.0% of children have a level of independence with the guidance of teachers and children begin to be independent. Early childhood language development that was cared for by working mothers showed that 85.0% were very good language development, 10.0% of children's languages ??began to develop, and 5.0% of children's language developed according to expectations. Whereas the language development of early childhood raised by non-working mothers showed that 35.0% were in very good language development, 55.0% of children's languages ??developed according to expectations, and 5.0% of children's languages ??began to develop. Second) There are significant differences in the independence and development of early childhood language between children cared for by mothers who work and do not work outside the home. There are some suggestions that the writer wants to put forward, including: PAUD Teachers are expected to be able to evaluate and develop activities that enhance early childhood independence; and, it is hoped that the results of the research can provide information to all parties, especially mothers, to pay more attention to the independence and development of early childhood language.